Hòa tách đồng kim loại từ bản mạch điện tử bằng dung dịch axit HNO3 - Long, Lê Hoàng; Hải, Huỳnh Trung; Jinki, Jeong; Jae-Chun, Lee (Vietnam Journal of Chemistry, 2012)
With the aim of recovering Cu from waste printed circuit boards (PCBs) in hydrometallurgical route, the HNO3 leaching of copper containing in the metal enriched fraction collected from previous study was studied. Parameters such as HNO3 concentration, initial temperature, agitation speed, and pulp density were investigated. The leaching rate of copper was almost independent of agitation speed and mainly dependent on HNO3 concentration, initial temperature and pulp density. 99% of Cu was leached within 30 minutes at 20% in HNO3 concentration, 50oC in initial temperature and 120 g/l in pulp density.